Optical properties of powder and ceramics of aluminium oxynitride obtained by self-propagating high-temperature synthesis - Akopdzhanyan, T.G.; Kondakov, A.A.; Rupasov, S.I.; Kozlova, A.P.; Pankratov, Vladimir (Lithuanian Physical Society, 2021)
The synthesis method of aluminium oxynitride (AlON) powders by nitriding of Al/Al2 O3 mixture under high-pressure nitrogen is proposed. The novelty of this method consists in adding KClO4 or Mg(ClO4 )2 and extra Al into the starting mixture (Al+Al2 O3 ) to cause the exothermal aluminium oxidation reaction, which therefore initiates the aluminium nitriding reaction. The microstructure and phase composition of the AlON powders obtained by self-propagating high-temperature synthesis are demonstrated by means of SEM and XRD analysis. Diffuse reflection spectra of AlON powders have been measured and the values of band-gap energy have been calculated. Optical transmission and reflection characteristics of the AlON ceramic samples sintered from AlON powders at 1930°C have been studied. The influence of the technological parameters of ceramics production on their transparency is revealed – the most transparent sample is obtained from the powders synthesized with the Mg(ClO4 )2 additive and sintered for 6 h. © Lietuvos mokslų akademija, 2021.
Savaime sklindančios aukštatemperatūrinės sintezės būdu gautų aliuminio oksinitrido miltelių ir jų keramikų optinės savybės
The reported study was funded by RFBR according to the Research Project No. 19-08-00655. V.P. acknowledges the State Research Program ‘Aug-stas enerģijas fizika un paātrinātāju tehnoloģijas’ (Projekta Nr. VPP-IZM-CERN-2020/1-0002). The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the H2020-WIDESPREAD-01-2016-2017-Teaming Phase2 under Grant Agreement No. 739508, Project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; AlON; Aluminium oxynitride; Combustion; Optical properties; Self-propagating high-temperature synthesis; Transparent ceramics